Effect of 6-Benzylaminopurine (BA) and Paclobutrazol (PBZ) with Light Intensity Variations for Cherry Tomatoes In vitro Flowering (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Utilization of Solanum lycopersicum L. and its varieties contribute to plant biotechnology to study the effect of genes and flower transition events. This study aims to optimize media and light intensity for in vitro flowering of a cherry tomato variety. Induction of flowering was carried out using seven types of media combined with 3 light intensities, followed by feeding by adding liquid medium MS+PBZ 1 mg/L. A positive response is shown at the light intensity of 2,600 lux; there are 5 explants that have flower buds. The percentage of flower buds for each treatment combination was 50% from two replications. The first shoots occurred at 142 days after planting (DAP) on explants grown on media containing 0.5 mg/L BA, 0.75 mg/L PBZ, with feeding treatment. It can also be assumed that the emergence of flower buds occurred not because of the PGR induction treatment, but because at that time the explants had entered the generative phase, considering that the plantlets had been growing for a long time. Although the effects of BA and PBZ have not been confirmed, the use of 2,600 lux light appears to be the best condition for cherry tomato in vitro flowering induction.